2011
DOI: 10.1111/j.1524-4725.2010.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Treatment with Triple Combination Cream and Intense Pulsed Light is More Efficacious than Sequential Treatment with an Inactive (Control) Cream and Intense Pulsed Light in Patients with Moderate to Severe Melasma

Abstract: The results of this study suggest that TC cream and IPL treatment is an effective and safe treatment option for patients with melasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 31 publications
0
44
0
1
Order By: Relevance
“…The TCC contained 4% hydroquinone, 0.05% tretinoin, and 0.01% fluocinolone acetonide. At week 10, 57% of patients in the IPL with TCC group were clear or almost clear in contrast to 23% of patients in the IPL with PC group (Goldman et al, 2011). A similar finding was reported by Figueiredo and Trancoso (2012) who compared outcomes of patients treated with IPL and TCC versus TCC therapy alone.…”
Section: Overview Of Laser- and Light-based Treatment Optionsmentioning
confidence: 86%
“…The TCC contained 4% hydroquinone, 0.05% tretinoin, and 0.01% fluocinolone acetonide. At week 10, 57% of patients in the IPL with TCC group were clear or almost clear in contrast to 23% of patients in the IPL with PC group (Goldman et al, 2011). A similar finding was reported by Figueiredo and Trancoso (2012) who compared outcomes of patients treated with IPL and TCC versus TCC therapy alone.…”
Section: Overview Of Laser- and Light-based Treatment Optionsmentioning
confidence: 86%
“…IPL uses high fluence of pulsed light and this high fluence of light carries higher risk of rebound hyperpigmentation after treatments (2,3). Patients on oral TNA experienced better results with IPL than patients with only IPL treatment (reduction of modified MASI score: 30.1% ± 21.1% vs.…”
Section: Discussionmentioning
confidence: 97%
“…No single treatment has been proven to be the most effective (2). Therefore, combination treatment using several possible modalities has been preferred and topical bleaching or whitening agents and/or chemical peelings along with laser-or light-based treatments have been generally adopted (3,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Thus logically a TC cream would have superior results to the chemical peel! This is highlighted by the studies where TC have been combined and compared with lasers and have been found to have superior results,[101112] which probably puts a question mark on the unnecessary use of lasers in melasma.…”
mentioning
confidence: 99%
“…The use of lasers for the treatment of melasma cannot be recommended as a first line treatment of melasma due to their unpredictable efficacy and safety. [101112131415161718192021222324] They can be considered as third line treatment when all other modalities have failed and patient wishes to try alternative treatment. Such treatments are not curative and should be made clear to patients when such treatments are offered to the patient.…”
mentioning
confidence: 99%